The international trends of inner wellness and its feasibility in the North Great Plain region, Hungary - a systematic review - József Márton PUCSOK; Melinda BÍRÓ; László BALOGH; András TATÁR; Péter HIDVÉGI; Andrea Puskás LENTÉNÉ (Editura Universităţii din Oradea, 2018)
In the 21th century there is an increased need for physical and psychological wellbeing. Inner wellness is a new form of wellness, which primarily focuses on active meditational practices and techniques in order to reduce the stress associated with daily living. The primary purpose of our study was to examine the international trends and current status of popular inner wellness activities such as Yoga, Tai Chi and its feasibility in Hungary's North Great Plain Region. The secondary purpose was to briefly investigate and summarize the mental and health benefits of Yoga and Tai Chi through systematically reviewing relevant literature, using scientific databases (Scopus, PubMed, Web of Science). Yoga and Tai Chi retreats have become more and more attractive among travelers. It would be necessary to establish several more resorts such kind in Hungary, in order to fulfill the needs of domestic and international visitors. After systematically reviewing related literature, we may conclude, that most of the studies found in major databases, examining Yoga or effect of Yoga therapy were conducted in a clinical setting. Traditional benefits of Yoga therapy are well-documented, however more high-quality, evidence-based research would be necessary to conduct in the future. In addition to that, these investigations should involve populations from recreational settings too, in order to examine the effect of Yoga on overall health status, and quality of life.